Medical Brain Drain: The Role of Job Attributes and Individual Traits - Marco Bertoni; Debdeep Chattopadhyay; Yuanyuan Gu (Health Economics, 2026)
ABSTRACT Medical brain drain poses a major challenge for health systems, reducing physician supply and undermining public investment in medical training. Prior work examined migration flows and their macroeconomic determinants. This study uses a discrete choice experiment to assess how individual background and personality traits shape medical student intentions to migrate and whether job attributes are valued differently at home and abroad. We surveyed 527 senior medical students from 12 Italian universities between November 2020 and July 2021, using Italy as a pertinent case given high physician emigration and limited inflow of foreign‐trained doctors. We find that students require compensation of around 30% of physicians' average starting salary to accept a job abroad rather than at home. Those from higher‐quality schools or medical families, and those who are more altruistic, competitive, and risk‐tolerant, require less compensation to migrate. Valuations of several job attributes also differ by location: at home, students value permanent contracts and professional development; abroad, they are willing to accept temporary contracts but reject under‐skilling. These findings suggest that emigration may disproportionately involve the best‐trained students. Policy simulations show that improving working conditions, job security, or professional development opportunities each substantially increases the predicted probability of choosing a domestic job, with salary increases having the largest effects.